(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Shalakya tantra, also known as Uttamanga Chikitsa, focuses on the vital sense organs situated above the Jatru-clavicle, addressing diseases of the head (Shiras), ear (Karna), eye (Netra), throat (Kanta), and nose (Nasa). The eye is considered as very important part of the body which performs the work of vision and due to its sensitive nature, it needs great care. Acharya Sushrutha outlines four treatment methods like Bheshaja, Shastra, Kshara and Agni karma as important treatment modalities. Anushastra karma are the para-surgical procedures, entail performing surgical interventions without the use of Shastras - sharp surgical instruments. Acharya Sushrutha has mentioned 14 types of Anushastras among which Jalaukavacharana, Agnikarma and Ksharakarma are given more importance and described in detail. Due to the pradhanyatwa of these three procedures in treatment they are also known as Trividha Anushastra karma. Along with Vata, Pitta and Kapha doshas, Rakta also plays a major role in causing different Netra rogas. So, it is advisable to go for safest Raktamokshana to do Dushita rakta dosha nirharana. In this article, an attempt is made to elaborate the complete knowledge of Anushastras used in different Netra rogas mentioned by our Acharyas. These procedures are simple, less time consuming, non-invasive, safe and cost-effective.